Effective training techniques - Broadwell, Martin M. (New York : American Management Associations, 1986)
This video gives you everything you need to train your new trainers, as well as supervisors and managers. It stars Martin Broadwell who has over 30 years experience in training
Pt.2. Presentation skill
Keywords: Employees -- Training of